All You Need Is Evidence: What We Know About Pneumonia in Children With Neuromuscular Diseases - Cherchi, Claudio; Chiarini Testa, Maria B.; Deriu, Daniele; Schiavino, Alessandra; Petreschi, Francesca; Ullmann, Nicola; Paglietti, Maria G.; Cutrera, Renato (Frontiers in Pediatrics, 2021)
Neuromuscular diseases may involve all major respiratory muscles groups including inspiratory, expiratory, and bulbar muscles. Respiratory complications are the major cause of morbidity and mortality. Pneumonia represents a frequent cause of morbidity in children with neuromuscular disease. The aim of this review is to collect knowledge about pneumonia in children with neuromuscular diseases. Pneumonia usually follows viral respiratory infections of the upper respiratory tract, due to the combination of an increased amount of nasal and oral secretions and an impairment of the cough efficiency and of the clearance of secretions due to the muscle weakness, further compromised by the infection itself. The accumulation of bronchial secretions leads to atelectasis and promote bacterial infection. Moreover, dysfunction of swallowing mechanism exposes these children to the risk of developing aspiration pneumonia. However, etiology of viral and bacterial respiratory infection in these patients is still poorly studied.